MANEJO DA IRRIGAÇÃO E ADUBAÇÃO NITROGENADA NO FEIJOEIRO – CULTIVAR PÉROLA - MACIEL, Gustavo de França; LOPES, Adriano da Silva; FRANCO, Jhonatan da Silva; Kraeski, Marcos Jefferson (ANAIS DO ENIC, 2024)
-